Toba batak cultural system towards the role of parents in supporting children's higher education in Bandar Pasir Mandoge - Br Sitorus, Faradiza Ariska; Susanti, Eka (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to analyze the influence of culture on the role of Batak Toba parents in supporting children's higher education in Bandar Pasir Mandoge. The Batak Toba people have a strong system of values and traditions, which affect various aspects of life, including education. The role of parents in supporting children's education is crucial for the success of higher education, especially in the midst of existing cultural and social challenges. This study uses a case study approach with a qualitative method, which involves in-depth interviews with parents, children who are pursuing higher education, and community leaders in Bandar Pasir Mandoge. The results of the study show that although the Batak Toba culture highly upholds family values and hard work, There are challenges in terms of adapting to the modern education system which requires a change in mindset and habits in supporting higher education. Batak Toba parents in Bandar Pasir Mandoge tend to support their children's education through moral and material motivation, although there are differences in their level of understanding of the importance of higher education. This study concludes that Toba Batak culture plays a significant role in shaping parents' attitudes and actions in supporting children's higher education, but there is a need to educate the public about the importance of cultural adaptation in the context of modern education.